Psychosocial Risk Factors of Myocardial Infarction: Turning Threat to Opportunity - Shah, Syed Imran Ali; Hamza, Muhammad; Saeed, Muhammad; Haq, Inamul (Nepalese Heart Journal, 2020)
Myocardial infarction (MI) is a major cause of mortality in the developing world. Modifiable risk factors of MI such as obesity, diabetes, smoking, high blood pressure and dyslipidemia are well known but besides these, there are many psychosocial factors that are independently related to MI. There is a striking dearth of reviews in the literature that examine, collate and summarize the impact of psychological contributors to MI. Present work was done to cover such gaps in knowledge and emphasize the need for psychological risk factors of MI to be considered while devising prevention guidelines and policies. Original research studies, meta-analyses and systematic reviews focusing on psychological factors in the development of MI were retrieved from databases including PubMed, Google Scholar, ProQuest, Elsevier, and Ovid Medline. Psychological factors like depression, anxiety, type A personality, stress, anger, hostility, social isolation and occupational stress were shown to feature consistently as risk factors for MI. Mitigating lifetime psychological distress may help decrease the disease burden of MI.